Hybridization quality and bond strength of adhesive systems according to interaction with dentin - Salvio, Luciana Andrea; Di Hipólito, Vinicius; Martins, Adriano Luis; de Goes, Mario Fernando (European Journal of Dentistry, 2013)
Objective: To evaluate the hybridization quality and bond strength of adhesives to dentin. Materials and Methods: Ten human molars were ground to expose the dentin and then sectioned in four tooth-quarters. They were randomly divided into 5 groups according to the adhesive used: Two single-step self-etch adhesives - Adper Prompt (ADP) and Xeno III (XE), two two-step self-etching primer systems - Clearfil SE Bond (SE) and Adhe SE (ADSE), and one one-step etch-and-rinse system - Adper Single Bond (SB). Resin composite (Filtek Z250) crown buildups were made on the bonded surfaces and incrementally light-cured for 20 s. The restored tooth-quarters were stored in water at 37΀C for 24 h and then sectioned into beams (0.8 mm 2 in cross-section). Maximal microtensile bond strength (μ-TBS) was recorded (0.5 mm/min in crosshead speed). The results were submitted to one-way ANOVA and Tukey′s test (α = 0.05). Thirty additional teeth were used to investigate the hybridization quality by SEM using silver methenamine or ammoniacal silver nitrate dyes. Results: SE reached significantly higher μ-TBS (P < 0.05); no significance was found between ADSE and XE (P > 0.05), and between SB and ADP (P > 0.05); ADSE and XE were significantly higher than SB and ADP (P < 0.05). The bonding interface of SB showed the most intense silver uptake. SE and ADSE showed more favorable hybridization quality than that observed for ADP and XE. Conclusions: The bond strength and hybridization quality were affected by the interaction form of the adhesives with dentin. The hybridization quality was essential to improve the immediate μ-TBS to dentin.
Keywords: Adhesive systems; ammoniacal silver nitrate; bond strength; hybrid layer; silver methenamine